2023
DOI: 10.18485/aeletters.2023.8.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Suitable Data Normalization Method to Combine with the CRADIS Method for Making Multi-Criteria Decision

Abstract: Compromise Ranking of Alternatives from Distance to Ideal Solution (CRADIS) is a new MCDM method (discovered in 2022). It is built on a combination of three well-known methods, including Additive Ratio Assessment (ARAS), Measurement Alternatives and Ranking according to Compromise Solution (MARCOS), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This method has the advantage of being resistant to the rank inversion phenomenon. However, if only the available data normalization (DN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…to energy, environment, sustainability, supplier selection, etc. [55], which confirms the justification of using this method in the selection of eco-friendly suppliers. This method was created based on the elements of three different multi-criteria analyses, namely ARAS, MARCOS, and TOPSIS [54].…”
Section: Fuzzy-rough Cradis Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…to energy, environment, sustainability, supplier selection, etc. [55], which confirms the justification of using this method in the selection of eco-friendly suppliers. This method was created based on the elements of three different multi-criteria analyses, namely ARAS, MARCOS, and TOPSIS [54].…”
Section: Fuzzy-rough Cradis Methodssupporting
confidence: 65%
“…The CRADIS method has so far been successfully used in solving to energy, environment, sustainability, supplier selection, etc. [55], w justification of using this method in the selection of eco-friendly supp was created based on the elements of three different multi-criteria ARAS, MARCOS, and TOPSIS [54]. There is something from each of t was incorporated into this method.…”
mentioning
confidence: 99%
“…In the case of weighting criteria using the LOPCOW method, both the RAM and PIV methods indicate that LO3 is the best option. These differences are understandable, as many studies have shown that rankings of options depend heavily on the method used for weighting and the MCDM method employed [3][4][5]. To determine which MCDM method is more suitable than the other two, it is necessary to test the stability of ranking options.…”
Section: Fig 2 Ranking Of Lubricant Typesmentioning
confidence: 99%
“…Two critical aspects in multi-criteria decision-making are the selection of methods to determine criterion weights and the choice of MCDM methods to be employed. These choices significantly impact the ranking of alternatives [3][4][5]. Weight determination methods are categorized into three groups: subjective methods, objective methods, and a combination of both, known as combined methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Data normalization is the process of bringing parameters with different units to a common dimensionless form [1,2]. This is one of the stages in multi-criteria decision-making processes [3].…”
Section: Introductionmentioning
confidence: 99%